Universal fine interpolation algorithms for accuracy improvements of industrial robots - Buschhaus, Arnd; Krusemark, Stefan; Karlidag, Engin; Franke, Jorg (International Conference on Ultra Modern Telecommunications & workshops, 2016)
Visual servoing possesses the capability to improve the absolute accuracy of jointed arm robots. In this context, an online closed-loop control of the tool center point movement offers the possibility to realize trajectories fulfilling high accuracy requirements. Thereby a robot independent external control efficiently interoperating with manufacturer specific robot controllers enables multifunctional usability. For a suitable external control, algorithms are needed, by which corrected movement instructions for each interpolation cycle are calculated, being compliant to the dynamic capabilities of different robot types. In the paper, control algorithms for calculating fine interpolation points are introduced, which serve the purpose of compensating positional deviations. The algorithm for compensating deviations on linear path segments is based on a movement orientation point forerunning the actual robots' position. In circular segments the corrective directional changes are limited to achieve smooth movement results. Multiple tests performed at real robot systems prove the effectiveness of the method.